A High‐Performance, Tailorable, Wearable, and Foldable Solid‐State Supercapacitor Enabled by Arranging Pseudocapacitive Groups and MXene Flakes on Textile Electrode Surface. (6th November 2020) - Wang, Yuanming; Wang, Xue; Li, Xifei; Li, Xiaolong; Liu, Yang; Bai, Yang; Xiao, Huanhao; Yuan, Guohui
Abstract: The challenges of solid‐state supercapacitors (SCs) for flexible and wearable electronics still remain in well balancing the electrochemical performance, mechanical stability, and processing technologies. Herein, a high‐performance, tailorable and foldable solid‐state asymmetric supercapacitor is developed via one‐step scalable chemical oxidization and MXene ink painting of N‐doped carbon fiber textile (NCFT) substrate. The employed O/N‐functionalized NCFT (ONCFT) and MXene materials under opposite potentials both incorporate excellent electrochemical behaviors of carbon‐like materials and pseudocapacitive materials, namely high rate capability and pseudocapacitance. By regulating oxidization time and MXene loading, the active layer of MXene decorated NCFT (MNCFT) and ONCFT electrodes analogously present tight skin structure, fundamentally avoiding the risk of active materials detaching from the support during mechanical deformation. As a result, the assembled MNCFT//ONCFT device not only achieves an extended voltage window of 1.6 V, high areal energy density of 277.3 μWh cm −2 and 90% capacitance retention after 30 000 cycles, but also experiences repeated folding tests. Additionally, the design makes it possible to tailor the textile‐based energy storage device (TEESD) into a designed size or shape without impairing its performance for device integration or shape conformable integration. Owing to the whole component fabrication being simple and scalable, the TEESD shows potential practical application. Abstract : A solid‐state asymmetric supercapacitor (ASC) is fabricated via one‐step scalable chemical oxidization and MXene ink painting of N‐doped carbon fiber textile (NCFT) substrate. The asymmetric device not only exhibits superior electrochemical performance but also delivers stable and remarkable energy storage performance during cycles of extreme deformation. In addition, the properties of good tailorability and device integration are achieved.